Synthesis of Nb2O5/C for H2O2 electrogeneration and its application for the degradation of levofloxacin - Valim, Ricardo Bertholo; Carneiro, Jussara Fernandes; Lourenço, Julio César; Hammer, Peter [UNESP]; dos Santos, Mauro Coelho; Rodrigues, Liana Alvares; Bertazzoli, Rodnei; de Vasconcelos Lanza, Marcos Roberto; da Silva Rocha, Robson (Springer Nature, 2024)
The present work sought to investigate H2O2 generation using a gas diffusion electrode (GDE) composed of carbon with niobium oxide for levofloxacin (LEVO) degradation. Results showed that the oxide formed was Nb2O5 (crystallographic structure was confirmed by XRD; chemical composition detected by XPS), and the increase in the Nb/C ratio led to more crystalline structure and higher crystallite size. The carbon with 5% Nb2O5 presented an average particle size of 5.6 nm, and this material led to the generation of the highest amount of H2O2 (317.6 mg L−1). The C/5% Nb2O5-modified GDE was applied for the degradation of LEVO in an acid medium in the presence and absence of Fe2+ ions. Long-term experiments conducted to analyze the time required for the total removal of LEVO showed that 96% of LEVO and 66% of organic load were removed in 270 min of treatment at the current density of 100 mA cm−2. Graphical abstract: (Figure presented.)
Keywords: Advanced oxidation process; Antibiotic degradation; Gas diffusion electrode; Hydrogen peroxide; Levofloxacin